Female desire, Puzzy Power and women-directed Scandinavian sex films. Issue 2 (1st June 2015) - Shriver-Rice, Meryl
Sweden and Denmark have a history of explicit cinema. In the later 1990s Lars von Trier's Zentropa became the first mainstream film company to produce female audience-centred explicit movies under the 'Puzzy Power Manifesto'. Following Puzzy Power, Scandinavian women directors continue to avoid male-centred perspectives while probing the boundaries of explicit imagery that remains empowering for women.